Improving Stock Price Prediction with GAN-Based Data Augmentation - Julisa Bana Abraham (Indonesian Journal of Artificial Intelligence and Data Mining, 2021)
The stock price is one of the most studied time series data because it is deemed to be profitable doing so, however stock price data is still difficult to predict because it is non-linear, non-parametric, non-stationary, and chaotic. One of the methods that most recently used to predict stock price data is deep learning. Although deep learning has a good performance to solve various problems, deep learning must be trained using a lot of data or this method will experience overfitting. This paper proposes a scheme to train a classifier model for predicting stock price time series data using augmented time-series data generated using GAN. Evaluation shows that the classifier model trained using augmented data has better performance on the AMZN dataset of 24.47% and 30.27% lower RMSE and MAE respectively compared to just using the real data and FB dataset of 15.84% and 13.88% lower RMSE and MAE respectively compared to just using the real data, but for the GOOG dataset it does not show a significant change in RMSE that is 0.52% lower and even the MAE value is increased slightly by 2.62% compared to just using the real data